Les Cobays Domestiques—The BecA Hub Domestic Cavies Project - International Livestock Research Institute (International Livestock Research Institute, 2014)
Food security is a real challenge in most parts of Africa. This is particularly so when the quantity and quality of animal-source foods are concerned. All over Africa, dietary protein remains very low. Regular supply of small quantities of animal protein has been shown to be crucial for adequate physical and cognitive development of children.